RANCANG BANGUN MODEL TEKNOLOGI INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) - Reda Rizal (Bina Teknika, 2016)
The research was reflected by the condition of the aquatic environment in the vicinity of settlements which is very poorly marked by physical-chemical data-biological water in drainage channels that are below the threshold value of the quality standards. Yet the availability management and waste water treatment technology source of household activities, small and medium. Research methods method using architecture models of technology waste water treatment plan which provides benefits on ecology, economy, social, culture and healthy, with a technology less pollution, water saving, and clean water. The research of technology waste water treatment plan is able to cleanse and purify waste water at the level of the quality of the raw water that meets the quality, and the collection of water pollutants at medium charcoal as an absorber that can be utilized as a fertilizer plant and as a high-energy fuel. The research designing the models of technology waste water treatment plan, the technology will produce low-cost, environmentally friendly and can be classified as sustainable technology.